Effect of transportation on E. coli O157:H7 prevalence and coliform concentrations in feces of feedlot cattle - Aperce, C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Foodborne illness from Escherichia coli O157:H7 is a major concern for the food industry. Contamination of food products can occur at slaughter by contact with hide or feces. Limiting E. coli O157:H7 shedding is important to prevent outbreaks. Previous studies have demonstrated a relationship between stress and levels of pathogens shed in feces. During transport to the slaughterhouse, animals are subjected to large amounts of stress. This stress could increase shedding of E. coli O157:H7 prior to slaughter, and in so doing increase the risk of contamination of beef products by contact with hides or feces. Our objective in this study was to evaluate the effects of transportation on fecal shedding of E. coli 4 and 24 hours after transport compared with non-transported animals.
Keywords: Beef; E. coli O157:H7; Coliform concentrations; Feedlot